'A dive into floods': Exploring the Dutch implementation of the floods directive - Van Eerd, M.; Dieperink, C.; Wiering, M. (IWA Publishing, 2015)
UBUlink(opens in a new window)|Entitled full text(opens in a new window)|View at Publisher(opens in a new window)| In recent years the number and frequency of high-impact floods have increased and climate change effects are expected to increase flood risks even more. The European Union (EU) has recently established the Floods Directive as a framework for the assessment and management of these risks. The aim of this article is to explore factors that have hampered or stimulated the implementation process of the Floods Directive in the Netherlands, from its establishment in 2007 until January 2013. During this period, the first requirements of the Floods Directive had to be implemented, while the second and third obligations were to be in an advanced stage. Following a literature review of policy implementation theories and a content analysis of the Floods Directive, we have studied the implementation processes in the Dutch part of the Meuse and Rhine-West catchments. Perceptions of interviewees and survey respondents were used to identify influential factors. Our research shows that although the implementation process in the Netherlands is on schedule, it is iterative and complex. Various constraining and stimulating factors, affecting the implementation process, are distinguished. The article concludes with some suggestions for improving the further implementation of the Floods Directive.
Keywords: Flood risk management; Floods Directive; Meuse river basin; Policy implementation; Rhine river basin; The Netherlands; Taverne; SDG 13 - Climate Action